Method for preparing flexible electrode by constructing gold nanowire film based on tellurium nanowire in-situ conversion

The construction of gold nanowire films through in-situ conversion of tellurium nanowire films solves the shortcomings in aspect ratio and conductivity of existing flexible gold nanowire film electrodes, and realizes an efficient and low-cost preparation process, which is suitable for a variety of application fields.

CN119876925APending Publication Date: 2025-04-25NANKAI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510073293.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing flexible gold nanowire film electrodes have shortcomings in aspect ratio and conductivity, and due to their large thickness, it is difficult to fit into curved surface shape, which affects signal transmission, especially in applications in the field of biomedical science.

Method used

The gold nanowire film is constructed through in-situ conversion of tellurium nanowire film, and the thickness of the gold nanowire is controlled to achieve high aspect ratio and good conductivity. At the same time, the process flow is simplified by electrostatic adsorption liquid phase assembly method and hydrothermal synthesis method.

Benefits of technology

The prepared gold nanowire film has high aspect ratio, good conductivity and tensile stability. It is suitable for a variety of flexible substrate materials, with low cost and simple process, and is suitable for wearable devices and flexible electronic skin fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876925A_ABST
    Figure CN119876925A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a flexible electrode by constructing a gold nanowire film based on tellurium nanowire in-situ conversion, which comprises the following steps: preparing a tellurium nanowire through hydrothermal synthesis, electrostatically adsorbing the tellurium nanowire film on a pretreated substrate, preparing a gold nanowire film by using an in-situ conversion method, transferring the gold nanowire film to a flexible substrate, and preparing the flexible electrode by using the gold nanowire film. And preparing the flexible gold nanowire electrode. The in-situ conversion method is simple in preparation step, low in production cost and high in material utilization rate and conversion efficiency, and meanwhile the original morphology structure of the tellurium nanowire film can be kept. Therefore, the prepared gold nanowire film has the characteristic similar to the high aspect ratio of the tellurium nanowire. In addition, the positive participation of tellurium atoms in the in-situ conversion process accelerates the conversion speed, so that the gold atom content and the conductivity are rapidly improved. The flexible substrate suitable for the thin film has various selections and can be selected according to different specific application requirements, so that the application range of the flexible substrate in the field of flexible electrodes is widened.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of flexible electrode preparation, and in particular relates to a method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires. Background Art

[0002] Nanowires, as one-dimensional nanomaterials, have been widely used in the field of flexible electrode preparation due to their unique physical and chemical properties. In particular, metal nanowires, such as gold nanowires, have shown great application potential in wearable devices, medical implants, and electronic skin due to their good conductivity, light transmittance, flexibility, and biocompatibility. However, there are relatively few studies on flexible gold nanowire thin film electrodes. One typical representative is the ultrathin gold nanowire film with a diameter of less than 2 nanometers and an aspect ratio of more than 10,000. The conductivity and deformation capacity of the flexible film prepared by interweaving and interlocking multiple ultrathin gold nanowires still do not meet the requirements of flexible electronics. On the other hand, the vertically arranged gold nanowire flexible electrode is composed of gold nanowires with a height of more than 500nm grown vertically on a flexible substrate, showing a unique enoki mushroom-like structure, and has excellent conductivity and tensile stability, which is suitable for high-performance soft bioelectronics and optoelectronics. However, due to their large thickness, vertically arranged gold nanowires may increase the overall thickness of the flexible electrode, making it difficult for the electrode to fit various curved surfaces, which in turn affects signal transmission. Especially in brain-computer interface applications in the biomedical field, the decrease in fit may reduce the efficiency and accuracy of signal transmission. In addition, the increase in the thickness of the conductive layer will also lead to a decrease in the transparency of the material, thus limiting its application in high-transparency fields. Summary of the invention

[0003] In order to solve the above problems, the present invention proposes a method for preparing a flexible electrode by directly in-situ conversion of a tellurium nanowire film into a gold nanowire film. The thickness of the gold nanowires prepared by this method is controlled between 35 and 40 nanometers, showing an extremely high aspect ratio (greater than 10,000), and the flexible gold nanowire film has good conductivity and tensile stability. In this process, the tellurium nanowires have a certain reducibility and participate in the in-situ conversion reaction, which not only provides tellurium atoms but also retains its original high aspect ratio nanowire structure. The in-situ conversion technology can complete the conversion without destroying the basic morphology of the nanowires, and maintains the morphological characteristics and network structure of the tellurium nanowires to a great extent, which is crucial for preparing a gold nanowire film with a high aspect ratio and a thin thickness.

[0004] The gold nanowire film provided by the present invention has low cost, short reaction time, simple preparation process and equipment, and the gold content of the converted gold nanowire exceeds 98%, and has a high aspect ratio (greater than 10,000), good conductivity and stability. At the same time, the gold nanowire film prepared by the present invention can be transferred to a variety of stretching substrates, such as hydrogenated styrene-butadiene-styrene block copolymer (SEBS), thermoplastic polyurethane elastomer (TPU), polydimethylsiloxane (PDMS) and Ecoflex and other flexible substrates.

[0005] To achieve the above purpose, the technical solution adopted by the present invention is:

[0006] A method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires, comprising the following steps:

[0007] (1) preparing tellurium nanowire solution by a hydrothermal synthesis method;

[0008] (2) After pre-treating the substrate, adsorbing the tellurium nanowire film of step (1) on the surface of the substrate by using an electrostatic adsorption liquid phase assembly method;

[0009] (3) immersing the tellurium nanowire film in a gold nanowire growth solution for rapid reaction to obtain a gold nanowire film;

[0010] (4) Spin coating a flexible substrate material onto the surface of the gold nanowire film, and peeling it off after solidification to obtain a flexible gold nanowire film electrode.

[0011] The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to the present invention specifically comprises the following steps:

[0012] In step (1), the tellurium nanowire raw material, ammonia water, hydrazine hydrate and an aqueous solution of polyvinylpyrrolidone (PVP) are mixed uniformly by magnetic stirring, and then subjected to hydrothermal reaction to obtain a tellurium nanowire mother liquor, which is centrifugally sieved to screen out tellurium nanowires with uniform diameter, and then dispersed in water to obtain tellurium nanowire solutions of different concentrations;

[0013] In step (2), the pretreatment is oxygen plasma hydrophilic treatment, and the assembly process adopts electrostatic adsorption liquid phase assembly method, which uses the attraction between positive and negative charges in the solution molecules to make substances with different charges attract each other to the position of common contact; preferably, a strong cationic polyelectrolyte, such as polydiallyldimethylammonium chloride (PDDA) and a negatively charged tellurium nanowire coated with PVP on the surface are assembled. The specific operation is: immerse the pretreated substrate in PDDA aqueous solution and let it stand, wash it with pure water and nitrogen, immerse it in the tellurium nanowire solution of step (1) and let it stand, the nanowires self-assemble on the substrate, and then wash it with pure water and nitrogen to obtain a tellurium nanowire film;

[0014] In step (3), chloroauric acid, 4-mercaptobenzoic acid, and L-ascorbic acid solution are mixed evenly to form a gold nanowire growth solution, and the tellurium nanowire film of step (2) is immersed in the gold nanowire growth solution for reaction, and then taken out and cleaned with anhydrous ethanol and nitrogen to obtain a gold nanowire film;

[0015] In step (4), a flexible substrate material is spin-coated on the surface of the gold nanowire film prepared in step (3), peeled off after thermal curing, and cleaned with nitrogen to obtain a flexible gold nanowire film electrode.

[0016] Furthermore, the solution for the hydrothermal reaction in step (1) is a mixed aqueous solution containing 2.5-3wt.% polyvinyl pyrrolidone, 0.5-0.7wt.% ammonia water, 1.2-1.5wt.% hydrazine hydrate and tellurium nanowire raw materials, the magnetic stirring speed is 400-700rpm, the hydrothermal reaction is carried out after stirring for 10-30min, the temperature is 150-200°C, and the time is 2.5-3.5h.

[0017] Furthermore, in step (1), the tellurium nanowire nanosheets and nanobelts are screened at a centrifugal speed of 5000-8000 rpm for 5-10 min, and the tellurium nanowires with uniform diameter are screened at a centrifugal speed of 14000-16000 rpm for 5-10 min.

[0018] Furthermore, in step (2), the oxygen plasma hydrophilic treatment power is 100-150 W, the time is 180-300 s; the mass fraction of the PDDA aqueous solution is 0.05 wt.%, the immersion time is 2-5 min; and the standing time in the tellurium nanowire solution is 2-5 min.

[0019] Furthermore, in step (3), the concentration of chloroauric acid is 3-9 mM, the concentration of 4-mercaptobenzoic acid is 0.2-0.75 mM, the concentration of L-ascorbic acid solution is 7-22 mM, and the reaction time of the tellurium nanowire film in the gold nanowire growth solution is 5-30 s.

[0020] Furthermore, in step (4), the flexible substrate material includes any one of hydrogenated styrene-butadiene-styrene block copolymer (SEBS), thermoplastic polyurethane elastomer (TPU), polydimethylsiloxane (PDMS) and Ecoflex.

[0021] Furthermore, in step (4), the SEBS solution is spin-coated at a speed of 2000-3000 rpm for 50-60 seconds, and the heating curing temperature is 80-100° C. for 10-20 minutes.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] (1) The present invention converts tellurium nanowires in situ, can precisely control the growth of gold nanowires, and provides an ultra-thin gold nanowire film with a high aspect ratio (greater than 10,000), a diameter between 35-40 nm, a gold content of more than 98%, and good stability and conductivity;

[0024] (2) The present invention is applicable to any substrate, and has a simple process flow, low cost, high efficiency, and can be prepared on a large scale at room temperature, providing a basic idea for commercial applications;

[0025] (3) The gold nanowire electrode prepared by the present invention forms a network structure and has the characteristics of high aspect ratio, etc. It still has the ability to stably transmit signals under 100% stretching, and can be applied to fields such as wearable devices and flexible electronic skin;

[0026] (4) The present invention is to convert tellurium nanowires into gold nanowires in situ. The tellurium nanowires can be patterned by photolithography, laser engraving and other processes, and the pattern is used as a template for conversion to prepare patterned gold nanowire electrodes; BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a physical picture of the tellurium nanowire film prepared in Example 1 of the present invention;

[0028] Figure 2 This is a scanning electron microscope photograph of the tellurium nanowire film prepared in Example 1 of the present invention;

[0029] Figure 3 This is a transmission electron microscope photo of the tellurium nanowire film prepared in Example 1 of the present invention;

[0030] Figure 4 This is a physical picture of the gold nanowire film prepared in Example 1 of the present invention;

[0031] Figure 5 This is a scanning electron microscope photo of the gold nanowire film prepared in Example 1 of the present invention;

[0032] Figure 6 The transmission electron microscope photo of the gold nanowire film prepared in Example 1 of the present invention (left) and the EDS image with a reaction time of 30 seconds (right);

[0033] Figure 7 X-ray diffraction analysis of the tellurium nanowire film (left) and the gold nanowire film (right) prepared in Example 1 of the present invention;

[0034] Figure 8 This is a graph showing the variation trend of the square resistance of the gold nanowire film prepared in Example 1 of the present invention with the reaction time;

[0035] Fig. 9This is a physical picture of the flexible gold nanowire film prepared in Example 1 of the present invention;

[0036] Fig.10 This is a graph showing the variation trend of the resistance of the flexible gold nanowire film prepared in Example 1 of the present invention with deformation; DETAILED DESCRIPTION

[0037] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the claims of the present invention.

[0038] Example 1

[0039] (1) A mixed aqueous solution containing 2.5-3wt.% polyvinyl pyrrolidone, 0.5-0.7wt.% ammonia water, 1.2-1.5wt.% hydrazine hydrate and tellurium nanowire raw materials is prepared in a reaction kettle, and the mixture is stirred at a magnetic stirring speed of 400-700rpm for 10-30min and then subjected to hydrothermal reaction, preferably at a temperature of 150-200°C and a time of 2.5-3.5h. The mixture is then naturally cooled to room temperature to obtain a tellurium nanowire mother solution;

[0040] (2) centrifuging the tellurium nanowire mother liquid at a speed of 5000 to 8000 rpm for 5 to 10 minutes, taking the supernatant, and then centrifuging it at a speed of 14000 to 16000 rpm for 5 to 10 minutes to obtain a tellurium nanowire precipitate with uniform diameter, and dispersing the precipitate in pure water to obtain a tellurium nanowire solution;

[0041] (3) performing oxygen plasma hydrophilic treatment on the glass substrate, preferably with a power of 100 to 150 W and a time of 180 to 300 s;

[0042] (4) Immerse the treated film in a 0.05wt.% PDDA aqueous solution, let it stand for 2 to 5 minutes, take it out, wash it with pure water and nitrogen, and then immerse it in the tellurium nanowire solution in step (1) and let it stand for 2 to 5 minutes, take it out, and rinse it with pure water and nitrogen to obtain a tellurium nanowire film deposited on a glass substrate; this method can be used for most substrates, and the present invention only uses a glass substrate as an example. The actual picture, scanning electron microscope picture, and transmission electron microscope picture of the tellurium nanowire film on the glass substrate are shown in FIG. Figure 1 , 2 , as shown in 3;

[0043] (5) preparing 3-9 mM chloroauric acid, 0.2-0.75 mM 4-mercaptobenzoic acid, and 7-22 mM L-ascorbic acid solution as a gold nanowire growth solution;

[0044] (6) The tellurium nanowire film on the glass substrate is placed in a gold nanowire growth solution and reacted for 5 to 30 seconds. The film is taken out and rinsed with anhydrous ethanol and nitrogen to obtain a gold nanowire film. The film resistance is tested using a digital four-probe tester. The physical image, scanning electron microscope image, transmission electron microscope image, X-ray diffraction analysis spectrum of the gold nanowire film on the glass substrate and the square resistance trend diagram with reaction time are as follows: Figure 4 , 5 , 6, 7, 8;

[0045] (7) The surface of the gold nanowire film on the glass substrate is spin-coated with SEBS solution at a speed of 2000-3000 rpm for 50-60 seconds, and heated at 80-100°C for 10-20 minutes. The film is then immersed in an ethanol culture dish and rinsed with nitrogen after automatic peeling to obtain a flexible gold nanowire film electrode. The film is then tested using a uniaxial stretching platform. The actual picture of the flexible gold nanowire film and the trend of resistance versus deformation are shown in FIG. Fig. 9 , 10 As shown;

[0046] It can be seen that: a method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires (ie, Example 1), the prepared tellurium nanowire film has a resistance of 10 6 Ω, put it into the gold nanowire growth solution for reaction. When the reaction time is 5s, the resistance drops to 39.61±1.88Ω / sq. When the reaction time is extended to 30s, the resistance further drops to 7.18±0.02Ω / sq, and the gold content exceeds 98% at this time. This shows that the conversion reaction of tellurium nanowires to gold nanowires is rapid, and the degree of conversion is positively correlated with the reaction time. As the growth time increases, the resistance value and the tellurium content will further decrease. This description only shows the efficient conversion process within 5 to 30s as an example. In addition, when the prepared flexible gold nanowire film electrode is 100% deformed, although the resistance rises to 91.55±0.05Ω / sq, it can still maintain stable output performance, meeting the requirements of the flexible electrode field for electrode performance, and is therefore suitable for wearable devices and flexible electronic skin and other application fields.

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires, characterized in that: The method comprises the following steps: (1) mixing tellurium nanowire raw materials, ammonia water, hydrazine hydrate and an aqueous solution of polyvinylpyrrolidone (PVP) uniformly by magnetic stirring, performing a hydrothermal reaction to obtain a tellurium nanowire mother liquor, performing centrifugal screening to screen out tellurium nanowires with uniform diameters, and then dispersing the mother liquor in water to obtain tellurium nanowire solutions of different concentrations; (2) After subjecting the substrate to oxygen plasma hydrophilization treatment, immersing it in a polydiallyldimethylammonium chloride aqueous solution PDDA and letting it stand, washing it with pure water and nitrogen, immersing it in the tellurium nanowire solution of step (1) and letting it stand, allowing the nanowires to self-assemble on the substrate, and then washing it with pure water and nitrogen to obtain a tellurium nanowire film; (3) mixing chloroauric acid, 4-mercaptobenzoic acid, and L-ascorbic acid solution uniformly as a gold nanowire growth solution, immersing the tellurium nanowire film in step (2) in the gold nanowire growth solution for reaction, then taking out and washing with anhydrous ethanol and nitrogen to obtain a gold nanowire film; (4) Spin coating a flexible substrate material on the surface of the gold nanowire film prepared in step (3), immersing the film in an ethanol solution after thermal curing, and cleaning the film with nitrogen after the film is automatically peeled off to obtain a flexible gold nanowire film electrode.

2. The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to claim 1, characterized in that: The solution for the hydrothermal reaction in step (1) is a mixed aqueous solution containing 2.5-3wt.% polyvinyl pyrrolidone, 0.5-0.7wt.% ammonia water, 1.2-1.5wt.% hydrazine hydrate and tellurium nanowire raw materials, the magnetic stirring speed is 400-700rpm, the hydrothermal reaction is carried out after stirring for 10-30min, the temperature is 150-200°C, and the time is 2.5-3.5h.

3. The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to claim 1, characterized in that: In step (1), the tellurium nanowires, nanosheets and nanobelts are screened at a centrifugal speed of 5000-8000 rpm for 5-10 min, and the tellurium nanowires with uniform diameter are screened at a centrifugal speed of 14000-16000 rpm for 5-10 min.

4. The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to claim 1, characterized in that: In step (2), the oxygen plasma hydrophilic treatment power is 100-150W, the time is 180-300s; the mass fraction of the PDDA aqueous solution is 0.05wt.%, the immersion time is 2-5min; and the standing time in the tellurium nanowire solution is 2-5min.

5. The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to claim 1, characterized in that: In step (3), the concentration of chloroauric acid is 3-9 mM, the concentration of 4-mercaptobenzoic acid is 0.2-0.75 mM, the concentration of L-ascorbic acid solution is 7-22 mM, and the reaction time of the tellurium nanowire film in the gold nanowire growth solution is 5-30 s.

6. The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to claim 1, characterized in that: In step (4), the flexible substrate material includes any one of hydrogenated styrene-butadiene-styrene block copolymer SEBS, thermoplastic polyurethane elastomer TPU, polydimethylsiloxane PDMS or Ecoflex.

7. The method for preparing a flexible electrode by constructing a gold nanowire film based on in-situ conversion of tellurium nanowires according to claim 1, characterized in that: In step (4), the SEBS solution is spin-coated at a speed of 2000-3000 rpm for 50-60 seconds; the heating curing temperature is 80-100° C. for 10-20 minutes.